GEOCHEMISTRY OF ALKALI AND ALKALINE EARTH METALS IN IRRIGATED LIGHT SIEROZEM SOILS (Scientific journal of the Fergana State University, 2026)
This paper presents a geochemical assessment of alkali (Na, K, Rb, Cs) and alkaline earth (Ca, Sr, Ba) metals in irrigated light sierozem soils of farms located in the Quvasoy district of the Fergana Valley, Uzbekistan. Soil profiles were sampled by genetic horizons from 0–20(25) to 120–150 cm, and total contents of selected elements were determined under laboratory conditions. The results show a clear dominance of Ca, relatively stable background levels of K and Na, trace amounts of Rb and Cs, and moderate accumulation of Sr and Ba. The vertical distribution of these elements is weakly differentiated, reflecting carbonate-rich parent materials, arid-continental climate and limited leaching under irrigation. The findings provide baseline information on alkali and alkaline earth metal contents in irrigated light sierozem soils of the Fergana Valley and support their agro-ecological evaluation and monitoring.